KEMISKINAN DAN POST-MODERNISME KEBUDAYAAN - Irianto, Agus Maladi (HUMANIKA, 2013)
ABSTRACT This article is a response to the book Death Without Weeping: The Violence of Everyday Life in Brazil, the work of Nancy Scheper-Hughes, University of California Press Berkeley and Los Angeles: 1992. Ethnographic work of the book is more likely to be in line with the thinking of post-modernism, which saw a radical change from an industrial to the postindustrial organized cultural consumption, mass media game, and the development of information technology. In addition to a combination of approaches-symbolic interpretivism approach and historical material- expressed on the issues of marginalization and contestation of power inherent in the post-modernism culture today. Keywords: poverty, marginalization, post-modernism culture